. Systematization and analysis of factors effecting tangential hardness of nominal stationary friction contact. - Мисліборський, В.В.; Костогриз, С.Г. (Problems of Tribology, 2015)
Tangential hardness of nominal stationary friction contact (NSFC), which characterizes its elastic properties under shifting has been analytically defined on the base of analysis of the research conducted on previous shifting in NSFC. It clearly identifies dependence of the initial tangential hardness on the three basic factors: nominal pressure in contact q, the ratio of the shear modulus G of contacting surfaces material to the Young’s modulus E; arithmetic mean deviation of surface profile Ra. As-suming all given above the conclusion can be made that direct effect on the initial hardness of the contact со can be performed by each of those factors separately, for an instance by nominal pressure, and by complex group of factors as well